1995
DOI: 10.1108/09534819510084337
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of team‐based management: a case study

Abstract: Team‐based management systems appear to be a possible avenue for increasing the productivity and effectiveness of organizations. However, there are concerns regarding their true purposes and effects within organizations. There is presently a dearth of literature evaluating the effectiveness of team‐based management. To begin filling this void, provides a case study illustrating the process, as well as the findings, from such an evaluation effort. In addition, presents a review of the literature regarding team‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Following this the question was asked, "What were the weaknesses of the program?" The literature review found authors such as Whitfield, Anthony, and Kacmar (1995), Kerzner (2000) and Dunn (2001) all claiming that a weakness of such a program was the difficulty in implementation due to the projects' time frames. This was also evident across both case studies, as both projects were allocated with little time to properly plan for such a program.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following this the question was asked, "What were the weaknesses of the program?" The literature review found authors such as Whitfield, Anthony, and Kacmar (1995), Kerzner (2000) and Dunn (2001) all claiming that a weakness of such a program was the difficulty in implementation due to the projects' time frames. This was also evident across both case studies, as both projects were allocated with little time to properly plan for such a program.…”
Section: Resultsmentioning
confidence: 99%
“…Although respondents recognized the importance of a skilled, experienced, expert, committed and focused team, there was no opportunity for them to employ this in the case studies. Whitfield, Anthony, and Kacmar (1995) identified this as a project team trait that would lead to increased effectiveness. Whitfield, Anthony, and Kacmar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bateman and Zeithaml (1990) opine that teamwork can increase competitiveness by: (i) improving productivity; (ii) improving quality and encouraging innovation; (iii) taking advantage of the opportunities provided by technological advantages; and (iv) improving employees motivation and commitment. Whitfield et al (1995) assert that team decision-making offer a number of advantages, which include (1) motivation through participation;…”
Section: Prospects Of Effective Team Spirit To Change Managementmentioning
confidence: 99%